AHF 2.0: um voo pelo ciberespaço por meio da escrita colaborativa na aula de Inglês - Oliveira, Sérgio Miguel Gartner Pais de (2015)
This research aims at describing and interpreting the collaborative writing in English (understood as a human experience phenomenon) developed by 9th grade students of a private Elementary School in Belo Horizonte (MG), from the complex thought perspective. The research involves the accomplishment of two writing assignments undertaken on the Google Docs plataform which uses Web 2.0 resources and whose goals were to motivate group work, practise writing skills in EFL, develop creativity, reflection, discussion and problem solving. The texts used for the interpretation of the phenomenon were collected from four online questionnaires. Records and comments written on students' work also served as textual material to understand the nature of the phenomenon studied. This research is primarily based on Morin`s notion of Complex Thought (1990, 2009, 2010) which can be understood as an open, inclusive and flexible thinking that sets a new look at the world, trying to understand the constant changes of the real world. The new paradigm dialogues with the opposite, with multiplicity, randomness, and uncertainty. Grounded on Complexity as the starting point, other theoretical components are also used to help the investigation, considering collaborative writing in teaching L2, procedural writing models, digital context of Web 2.0 and collaborative learning. These constructs interact with each other and are important for understanding the context of the research, as well as its characteristics and uniqueness. To conduct this research, a qualitative methodology is adopted, specifically, the Hermeneutic- Phenomenological Approach, according to Freire‟s (1998, 2007, 2009, 2010, 2012) and van Manen`s (1990) perspectives. This study reveals that the collaborative writing in digital context is structured around three comprehensive themes environment, interaction, tasks which are subdivided in subthemes that unveil the nature of the phenomenon under investigation. Based on the research undertaken it is possible to assert that collaborative writing in the digital environment can lead to new paths to a theory of writing in L2, engendering collaborative projects focused on writing in a foreign language. This study demonstrates that learners can develop communication and cooperation skills, as well as the development of critical thinking when there is a conducive learning environment for interaction